(untitled) (Advenimiento, 2021)
The idea of discipleship is not a new one in the New Testament. We find this practice established in the Old Testament. Moses did it with Joshua. David also guided and prepared his son Solomon for being a king. But the experience of Elijah as mentor and Elisha as his disciple requires a special attention. Since there are many similarities between them and what we found in the Gospels and the book of Acts about discipleship, this research compares the experiences of both OT prophets with Jesus and his disciples following the principles of the biblical typology. The goal of this study is to highlight these connections and learn some principles about discipleship for our church today.